(untitled) (Homoeopathy for All, 2025)
There are about 103 undergraduate and 57 postgraduate homoeopathic medical colleges in India, permitted by National Council for Homoeopathy (NCH), for admission during the sessions 2024-25 & 2025-26. Having the largest infrastructure in terms of colleges, in comparison to other countries, their contributions in the field of research are not so much encouraging. If we meticulously analyse different factors behind such inadequate research outputs, the following issues will generally come to our minds,